Kenya : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2008)
In Kenya, the general government is not defined consistently with government finance statistics (GFS) principles. Relationships between the central government and public nonfinancial and financial corporations are generally clearly defined. Government holdings of fully owned corporations and equity are moderate, and the management of state assets is clearly defined. The legislative basis for taxation is clear and comprehensive. Tax administration is clearly defined and well coordinated with overall fiscal management. External scrutiny of macroeconomic assumptions is encouraged. Kenya meets some of the requirements of the fiscal transparency code.